Changes in inflammatory balance correlates with conversion to psychosis among individuals at clinical high-risk: A prospective cohort study. (December 2022) - Zhang, TianHong; Zeng, JiaHui; Wei, YanYan; Ye, JiaYi; Tang, XiaoChen; Xu, LiHua; Hu, YeGang; Cui, HuiRu; Xie, YuOu; Tang, YingYing; Liu, XiaoHua; Liu, HaiChun; et al.
Highlights: The baseline interleukin (IL)-1β/IL-6 ratio changes in individuals with clinical high risk who convert to full psychosis. A specific CD4-expressing T helper cell type 1 (Th1) and type 2 (Th2) cytokine imbalance is associated with an increased risk of developing psychosis. The interleukin (IL)-1β/IL-6 ratio is a significant predictor of the subsequent conversion to psychosis. Abstract: Previous studies have revealed that the imbalance between Th1 cytokines and Th2 cytokines plays a role in disturbance of cellular responses in the brain during psychosis. Cross-sectional studies have implied that inflammatory cytokine changes emerge in early psychosis, even at the at-risk stage. This study aimed to test the hypothesis that inflammatory imbalance in clinical high-risk (CHR) individuals is associated with an increased risk of future psychosis. A prospective case-control study was performed to assess the Th1(interleukin (IL)-1β)/Th2(IL-6) balance in 84 CHR individuals and 65 age- and sex-matched healthy controls (HC). Serum IL-1β and IL-6 levels were measured by enzyme-linked immunosorbent assay at baseline and 1-year after the completion of the clinical assessment. Sixteen (19.0%) CHR participants converted to full psychosis during the 1-year follow-up period. At baseline, serum IL-1β level was significantly lower in the CHR-converter group - resulting in decreased IL-1β/IL-6 ratios – compared to those of the CHR-non-converter and HC groups. At the 1-year follow-up, IL-1β level had decreased, and IL-1β/IL-6 ratios had decreased in the CHR-non-converter group, such that these were comparable to values in the CHR-converter at this time point. Analysis of the changes in IL-1β/IL-6 ratio between the baseline and 1-year follow-up measurements identified different trajectories in the CHR-converter and CHR-non-converter groups. Our findings demonstrate that a specific pattern of Th1/Th2 imbalance (decreased IL-1β/IL-6 ratios with lower serum IL-1β level) is associated with an increased risk of developing psychosis. Such specific pattern has potential for predicting conversion outcomes and selecting a distinct subgroup of CHR with immune-imbalanced-phenotype, that relevance in precise prevention.